TINGKAT EFISIENSI SALURAN PEMASARAN KOMODITAS BERAS (Studi Kasus: Desa Polenga Kecamatan Watubangga Kabupaten Kolaka) - Campina Illa Prihantini; Budi Samudra; Yuli Purbaningsih; Lian Yunike; Indriani Nurul Suraturohmi; La Sisi (Universitas Galuh, 2022)
The number of rice production produced by Kolaka Regency is included in the five largest in Southeast Sulawesi Province. It is interesting to study whether this fact has a real impact on farmers as the first marketing agency. Polenga Village was chosen as the research location because this village is one of the largest rice-producing villages in Kolaka Regency. Writing this article aims to 1) identify rice marketing patterns in Polenga Village, 2) analyze the amount of marketing margin in Polenga Village, and 3) analyze the functions of marketing institutions carried out by each rice marketing agency in Polenga Village. This type of research is descriptive, qualitative and quantitative. Sources of data in this study, namely primary data obtained from respondents and secondary data obtained from agencies related to the research. The analysis carried out is the analysis of marketing margins and analysis of the functions of marketing institutions. The results showed that there were three main patterns of rice marketing in Polenga Village, namely: (I) from farmers directly to consumers, (II) from farmers to collectors and then to consumers, and (III) from farmers to collectors to retailers and ends up in the consumer. The second finding is that the highest marketing margin value is in Marketing Channel III, which is IDR 1.000 per kilogram. Meanwhile, in the second marketing channel, only IDR 500 per kilogram and the marketing channel I no marketing margin was found. Based on the analysis of the functions of marketing institutions, each institution has performed three main functions of marketing institutions, namely the physical function, the exchange function, and the facility function. The conclusion that can be drawn is that the most efficient marketing channel is Marketing Channel I where no marketing marjin is found and direct sales occur to consumers.